DETERMINATION OF ORGANIZATIONAL CLIMATE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH TRUST MEDIATION IN THE HOTEL BUSINESS IN SERANG CITY, BANTEN - Ika Pratiwi; Nancy Yusnita; Hamzah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Employees are an important part of the sustainability of the hotel business. However, in Serang City, which is one of the provinces with quite diverse tourist destinations, it is not supported by quality human resources so that businesses in this field are less developed. The purpose of this study is to determine the effect of climate organization on OCB; determine the effect of servant leadership on OCB; determine the effect of trust on OCB; determine the effect of climate organization on trust; determine the effect of servant leadership on trust; determine the effect of servant leadership on trust; determine the effect of climate organization and on OCB through trust; and determine the effect of servant leadership and on OCB through trust. This study uses a quantitative approach. The data used are primary and secondary data, primary data obtained from the results of questionnaires and interviews while secondary data obtained from scientific notes, journals and reports. Data analysis using SEM-PLS. SEM-PLS results show that climate organization, servant leadership and trust have an effect on OCB. Other results are also explained in this study and the limitations of the research will be explained thoroughly.